Substitusi Tepung Bungkil Kedelai dengan Fermentasi Daun Lamtoro (Leucaena glauca) Terhadap Pertumbuhan dan Efisiensi Pakan Ikan Nila (Oreochromis niloticus) [Subtitution Of Soybean Meal With Fermented Lamtoro (Leucaena glauca) On Growth And Feed Efficiency Of Tilapia Fish (Oreochromis niloticus) ] - Agustono Agustono; Novi Krishatno Putera; Sri Subekti (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Tilapia fish (Oreochromis niloticus) was known as an important commodity in the world's freshwater. Tilapia fish (O. niloticus) was a omnivores species of fish, which means that can eat plants and animals. Tilapia fish easy to breed, fast growing, relatively has large body size, disease resistance, easy to adapt to the environment, the price was relatively cheap and has a high nutritional value as a source of animal protein. One of the obstacles faced in the feed manufacturing was an expensive raw material availability, therefore, necessary to find alternative feed ingredients that were cheap, quality and be available at all the times. The purpose of this study was to determine the effect of the use lamtoro were fermented with probiotic on growth and feed efficiency of tilapia fish. The research was conducted at the Faculty of Fisheries and Marine University. This study was conducted for 42 days from 25 March - 5 May 2013. The research design used was a completely randomized design (CRD). Materials used in this study was tilapia fish aged 1 month, the body length ranges between 3-5 cm and body weight ranged from 1,3-1,5 gram as 100 individuals. Form of feed pellets substituted with lamtoro fermented dose A. 0% (control), B. 10%, C. 20%, D. 30%, E. 40% with 4 replications. The main parameters observed in this research were the growth rate and feed efficiency. Support parameters was the quality of water. Based on the results of research about substitution of soybean meal with fermented lamtoro in the feed rations were no significantly different effect on the rate of growth and feed efficiency (p> 0.05) due to dissolved oxygen content does not qualify as well as, higher quality feed than feed quality substituted.